2019
DOI: 10.1111/pcmr.12789
|View full text |Cite
|
Sign up to set email alerts
|

IL‐17A is not a treatment target in progressive vitiligo

Abstract: Multiple reports confirm elevated circulating IL‐17 levels and increased numbers of Th17 lymphocytes in patients with non‐segmental vitiligo. Additionally, melanocyte damaging characteristics have been ascribed to IL‐17. A single‐arm pilot study using secukinumab in active non‐segmental vitiligo was conducted. The large majority of patients developed additional skin depigmentations limiting further enrollment. Overall, laboratory analysis revealed no change in secreted chemokines or Th subsets. Th17 lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 19 publications
1
59
0
Order By: Relevance
“…The authors of that study concluded that the blockade of IL‐17A receptors could be a therapeutic target in vitiligo. A recent pilot study, however, failed to show any benefit of secukinumab, an IL‐17 inhibitor, in 8 patients of progressive, non‐segmental vitiligo. The study proposed that the raised IL‐17 level in vitiligo was due to the increased percentage of Th17.1 cells instead.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study concluded that the blockade of IL‐17A receptors could be a therapeutic target in vitiligo. A recent pilot study, however, failed to show any benefit of secukinumab, an IL‐17 inhibitor, in 8 patients of progressive, non‐segmental vitiligo. The study proposed that the raised IL‐17 level in vitiligo was due to the increased percentage of Th17.1 cells instead.…”
Section: Discussionmentioning
confidence: 99%
“…The same result was observed in our trial using secukinumab in progressive vitiligo which showed that 7/8 patients developed new skin depigmentations leading to an early halt of further recruitment. In subsequent experiments, we showed that Th17.1 cells rather than Th17 cells are increased in active vitiligo (11). Th17.1 lymphocytes are a subgroup of Th17 cells gradually differentiating into non-classical Th1 cells.…”
Section: Disorders Based On Targeted Immune-based Cell Destruction: Amentioning
confidence: 84%
“…Several promising results have been obtained by the off-label use of biologics and by pilot trials (Table 1, Figure 1) although disappointing results can be equally important to clarify the underlying pathogenic pathways. Failure of both TNF-α inhibitors and IL-17A-blockers in alopecia areata and vitiligo limits the involvement of these cytokines in the immune-mediated destruction of skin cells (10, 11). However, the apparent efficacy of TNF-α inhibitors in toxic epidermal necrolysis and occasional cases of alopecia areata and vitiligo suggest that the role of TNF-α is more complex (4, 7, 91).…”
Section: Discussionmentioning
confidence: 99%
“…Based on data supporting increased levels of Th17-related cytokines, such as IL-17 and IL-23, in the blood and skin of vitiligo patients, targeting the IL-23/IL-17 immune axis might represent another option for patients with vitiligo [ 55 , 66 ]. However, a recent clinical trial evaluating the efficacy and safety of secukinumab, a monoclonal antibody directed against IL-17, was prematuraly stopped due to the absence of clinical improvement, with worsening of the disease observed in some patients [ 67 ].…”
Section: Blocking the Initiation And Restraining The Progression Of Tmentioning
confidence: 99%